Income Analysis Of Duck Farming Business In Kedawung District Sragen Regency - Widianti, Alfina; Dewi Lestari, Retna; Rahyunanto, Setyo (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze the income factors of duck farming in Kedawung District, Sragen Regency because the majority of the population in the district work as duck farmers. Farmers feel the increase in feed prices caused by the El Nino phenomenon. The price increase will affect production costs. This study analyzed the income of duck farming businesses in Kedawung District where the majority of the population works as duck farmers. This study analyzed production costs, total revenue in one year to determine the total income received. The analysis method used is income analysis, with the formula total revenue minus total production costs. Total revenue can be known from the selling price multiplied by the yield. The results of this study are the total revenue of each farmer in Kedawung Subdistrict, Sragen Regency per year amounting to Rp 23,150,160 while the total costs per year incurred amounted to Rp 18,644,037. By subtracting the total revenue from the total production cost, the net income or profit per year is Rp 4,506,123. The calculated average income per month is IDR 403,456. This figure shows the amount of average income earned by household-scale duck farmers in Kedawung District every month of the year.